PENGELOLAAN PEMBELAJARAN SENI BUDAYA DI SMA - Cahya Isten; Rohiat Rohiat; Puspa Djuwita (Manajer Pendididikan, 2017)
Objectively this research is to describe the management of art and culture learning in SMA Negeri 3 Bengkulu Selatan. This research is a qualitative descriptive research that is a research from seseoranag subjects that have the characteristics that the data provided is the original data that can not be changed as well as using systematic way and can be accounted for kebenarnnya. In the data collection researcher using observation, interview and documentation. Research subjects include: principals, curriculum representatives, art and cultural teachers, and students. From this research, it can be seen that the management of art and culture in SMA Negeri 3 Bengkulu Selatan run effectively in accordance with government regulations as outlined in technical guidance of Education Unit Level Curriculum (KTSP).